Top of tide: Nexus between organization agility, digital capability and top management support in SME digital transformation - Mengxin Zhang; Xihui Chen; Hongming Xie; Luca Esposito; Anna Parziale; Shilpa Taneja; Ahsan Siraj (Heliyon, 2024)
In the swiftly evolving business landscape, digital transformation (DT) has emerged as a crucial strategy for firms to gain a competitive edge. Despite the abundance of literature on DT in firms, there remains a dearth of empirical research that defines and analyzes crucial antecedents of small and medium-sized enterprises’ (SMEs) DT from an internal perspective. To fill this research gap, this study examines the correlation between organizational agility and digital capability in cultivating SMEs' DT while also evaluating top management support as a moderating variable through the lens of internal factors of SMEs. The results indicate that both organizational agility and digital capability have a positive impact on SMEs' DT, with organizational agility significantly influencing digital capability. Furthermore, the findings highlight that digital capability serves as a mediator between organizational agility and SMEs' DT. In addition, top management support plays a moderating role in these relationships to a certain extent. Additionally, we explicate the concept of digital capabilities from the perspective of dynamic capability. Our study contributes to an enhanced understanding of the effect of organizational agility and digital capability on SMEs' DT, as well as the role of top management support. We provide recommendations for managers to enhance organizational agility and suggest that SMEs should improve their digital thinking to better perceive digital technology changes, enhance digital operation capabilities, and better integrate digital resources.